Analisis Kinerja Karyawan PT. Pembina Abadi Permai Ditinjau dari Kompensasi, Motivasi dan Kepuasan Kerja - Yulianti, Prima; Putri, Adinda Esa (LPPM Universitas Dharma Andalas, 2023)
This study aims to determine the effect of compensation, motivation and job satisfaction on employee performance at PT. Pembina Abadi Permai. The population in this study were all employees of PT Pembina Abadi Permai, totaling 72 employees. The sampling technique uses the total sampling method or the saturation method. The data analysis used is Statistical Product and service solutions (SPSS). Based on the research results, the results are summarized as follows (1) partial compensation has a positive and significant effect on employee performance at PT. Pembina Abadi Permai. (2) motivation partially has a positive and significant effect on employee performance at PT. Pembina Abadi Permai. (3) job satisfaction partially has a positive and significant effect on employee performance at PT. Pembina Abadi Permai. (4) Compensation, Motivation and Job Satisfaction simultaneously have a positive and significant effect on employee performance at PT. Pembina Abadi Permai